Influence of Recorded Pattern on Background Interference impact in Magnetic Recording - Nuttapon Chaiduangsri; Somyot Kaitwanidvilai; Damrongsak Tongsomporn (My University, 2021)
Abstract This paper discusses the impact of background interference on a recorded pattern for heat-assisted magnetic recording technology (HAMR). Several patterns of the background track were examined, with the log bit error rate and signal to noise ratio measured via a spin-stand tester using HAMR head and media. It was found that the low frequency pattern gave the highest BER and SNR loss due to the strong magnetic field from the adjacent tracks. Similar to its practical use, the PRBS pattern also showed high interference. These observations may be used to support HDD areal density growth.
Keywords: Area density; Heat-assisted magnetic recording; Patterned media; Surface Roughness and Optical Measurements